Not all folk-economic beliefs are best understood through our ancestral past. (30th August 2018) - Bhattacharjee, Amit; Dana, Jason
Abstract: We applaud Boyer & Petersen's (B&P's) approach to a fascinating topic. Their arguments against understanding folk-economic beliefs (FEBs) in terms of economic ignorance or specific biases, however, are overly pessimistic. Economic theory is the reason beliefs about such disparate phenomena are labeled "economic" and "folk." More importantly, some FEBs are better understood by examining current rather than ancestral contexts of exchange.